Effective removal of lead(II) from wastewater by amine-functionalized magnesium ferrite nanoparticles - Nonkumwong J. (2017)
© The Royal Society of Chemistry 2016. Mesoporous amine-functionalized magnesium ferrite nanoparticles (MgFe 2 O 4 -NH 2 NPs), with maximum magnetization of around 35 emu g -1 , were successfully synthesized and simultaneously functionalized under a refluxing condition by using ethanolamine as a surface modifier. The grafting of amine groups onto the MgFe 2 O 4 NPs was clearly confirmed by the Fourier transform infrared spectrum. Adopting the MgFe 2 O 4 -NH 2 NPs as a magnetic nanoadsorbent for Pb 2+ removal from simulated wastewater containing heavy metals is reported. Characterizations of the adsorption ability of MgFe 2 O 4 -NH 2 nanoadsorbent as a function of aqueous solution pH, initial Pb 2+ concentration and agitating time, as well as their adsorption kinetics and adsorption isotherms, were also performed. The adsorption of 25 mL of 10 mg L -1 Pb 2+ initial concentration onto 25 mg of MgFe 2 O 4 -NH 2 nanoadsorbent reached equilibrium within 10 min at pH 4 with 99% removal efficiency. Kinetics and isotherms of the adsorption were fitted with pseudo-second-order model and Langmuir model, respectively, indicating the strong chemisorption through coordinative bond formation between the amine groups and Pb 2+ ions. This MgFe 2 O 4 -NH 2 nanoadsorbent possesses a maximum capacity, calculated from Langmuir equation, of around 135.1 mg g -1 , which is higher than those of typical amine-functionalized adsorbents. Also, the selectivity experiments show that the MgFe 2 O 4 -NH 2 nanoadsorbent provides higher selectivity coefficient values for Pb 2+ than Ca 2+ , Cd 2+ , Zn 2+ , Cu 2+ and Ni 2+ .